The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pbio.1001462
|View full text |Cite
|
Sign up to set email alerts
|

Neural Activity during Natural Viewing of Sesame Street Statistically Predicts Test Scores in Early Childhood

Abstract: Neural activity that is evoked naturalistically in children during educational television viewing can be used to predict math and verbal knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
178
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(200 citation statements)
references
References 28 publications
(45 reference statements)
14
178
0
1
Order By: Relevance
“…This 5-min fMRI scan is described in detail elsewhere (20). For present purposes, only two contrasts were used: language processing (sentence reading plus sentence listening relative to rest) and mental calculation (mental processing of simple subtraction problems, such as 7 − 2, presented visually or auditorily, and contrasted to the processing of nonnumerical visual or auditory sentences of equivalent duration and complexity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This 5-min fMRI scan is described in detail elsewhere (20). For present purposes, only two contrasts were used: language processing (sentence reading plus sentence listening relative to rest) and mental calculation (mental processing of simple subtraction problems, such as 7 − 2, presented visually or auditorily, and contrasted to the processing of nonnumerical visual or auditory sentences of equivalent duration and complexity).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a bilateral inferior temporal region is activated by the sight of number symbols, such as Arabic numerals, but not by visually similar letters (18). Those regions lie outside of classical language areas, and several functional MRI (fMRI) studies have confirmed a double dissociation between the areas involved in number sense and language (19,20). Only a small part of our arithmetic knowledge, namely the rote memory for arithmetic facts, encoded in linguistic form (16,21).…”
mentioning
confidence: 99%
“…In other words, those children who exhibited a larger symbolic ratio effect on activity in the left IPS also displayed relatively stronger performance on the standardized tests of speeded arithmetic. In another set of recent studies (Cantlon & Li, 2013;Emerson & Cantlon, 2012), children viewed educational videos (Sesame Street) that had mathematical content, while their brain activity was recorded using fMRI. The degree of activity coupling (functional connectivity) between frontal and parietal brain regions during the viewing of these clips as well as how similar the brain activation of children was to that of a group of adults was found to be related to standardized measures of children's mathematics achievement.…”
Section: Brain Imaging Datamentioning
confidence: 99%
“…Already, studies have shown that analyzing brain activity during the full length of watching a movie allows for a more accurate prediction of academic performance (Valkanova et al 2014;Cantlon and Li 2013) as well as increased accuracy in detecting individual patterns of functional connectivity (Vanderwal et al 2017) compared to measuring brain activity during rest or an experimental task. Artificial intelligence, facial expression and eye tracking, portable head scans, virtual reality, and filming behavior are just examples of methods that will allow studying and analyzing participants in more naturalistic settings, minimizing confounding factors and enabling a richer signal.…”
Section: Going Forwardmentioning
confidence: 99%